Detection of the effects of restoration on community composition in a calcareous grassland: Does scale matter?. (16th January 2014) - Maccherini, Simona; Santi, Elisa; Marignani, Michela
Abstract The importance of the scale of observation in vegetation science has long been recognized. We have evaluated the effect of grain (plot dimension) on the detection of changes induced by shrubs cutting on plant composition of a calcareous grassland in Southern Tuscany (Italy). We conducted a 2‐year before 2‐year after‐control‐impact (BACI) field sampling design. We collected the cover of vascular plants using nested square quadrats with 0.5, 1 and 2 m sides. Any deviation of the restored plots from the control was analyzed by using the principal response curve (PRC) technique. Differences between the control and the restored plots, in time, accounted for 4.5, 3.3 and 7.4 of the between‐plot variation in species composition, respectively for 0.25, 1 and 4 m2 plots, but only the first PRC component of the largest scale was statistically significant. The results showed that the ability to differentiate the control from the restored plots, changed with increasing grain size although we did not obtain a monotonic behavior of the variance explained by the multivariate model. Including the assessment of scale dependence in the monitoring project appears useful and necessary to correctly evaluate the effects of restoration actions in a consistent way.